Analytical model for high temperature wear in thermal barrier coatings under non-steady state conditions in gas turbines (2012)
Abstrac: The continuously growing tension over energy resources in the context of a globalized and competitive economy demands more efficient ways to exploit those available resources; it is not possible to consider the energy generation process and the cogeneration outside this scenario, it is the reason why is necessary to work always at limit of the possibilities and that is where the development of engineering materials becomes a compulsory transit route. It is clear in light of the history of thermal engines, the efficiency is directly related to the development of stable materials at high temperatures, and it is precisely the field which aims to make inroads with this project, addressing the problem from the phenomenological point of view, where the key is to fully understand the physical processes of energy transformation to find, from this understanding, appropriate models to estimate the service life of the components of the gas turbines and others thermal engines.